2023
DOI: 10.4088/jcp.22m14674
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine/Samidorphan in Young Adults With Schizophrenia, Schizophreniform Disorder, or Bipolar I Disorder Who Are Early in Their Illness

Abstract: Objective: Patients with early-phase schizophrenia or bipolar I disorder (BD-I) are at greater risk for antipsychotic-associated weight gain. This 12-week, randomized, double-blind study conducted between June 2017 and December 2021 evaluated weight effects of combination olanzapine and samidorphan (OLZ/SAM) versus olanzapine in early-phase illness. Methods: Young adults (16-39 years) with DSM-5 schizophrenia, schizophreniform disorder, or BD-I, < 4 years since symptom onset, body mass index < 30 kg/m 2 , and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…During the preliminary assessment of the title and abstract, 163 duplicate and 55 irrelevant studies were removed. Furthermore, after excluding 14 studies by further reading their full texts, only five studies 14 , 15 , 18 , 24 , 25 were included in this meta-analysis, all from the English literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the preliminary assessment of the title and abstract, 163 duplicate and 55 irrelevant studies were removed. Furthermore, after excluding 14 studies by further reading their full texts, only five studies 14 , 15 , 18 , 24 , 25 were included in this meta-analysis, all from the English literature.…”
Section: Resultsmentioning
confidence: 99%
“…Another systematic review on the application of SAM in conjunction with OLZ for the treatment of SCZ and bipolar I disorder found 17 that the combination therapy tended to reduce weight gain in adult patients with SCZ compared to OLZ monotherapy, however, there was no significant difference in metabolic effects. Subsequently, two studies 18 , 19 on the treatment of SCZ with the OLZ/SAM were reported, and one randomized controlled trial (RCT) confirmed that 18 OLZ/SAM treatment decreased the risk of weight gain. Briefly, higher-quality evidence regarding the specific reduction of weight gain and metabolic disturbances induced by OLZ during treatment of SCZ with OLZ/SAM is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…As a second-line intervention, pharmacological treatment of metabolic alterations and weight loss treatment in PSD patients may be considered and is discussed in detail elsewhere ( 96 , 105 108 ) and in Section 4.4. Concerning non-pharmacological and mixed interventions for metabolic dysregulation in PSD, a systematic review of 23 randomized controlled trials suggested that cognitive/behavioral interventions and pharmacological adjuncts both showed modest but significant effects in preventing weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…If the patient has not successfully reached their targets after 3 months, pharmacological interventions such as anti-hypertensive, lipid-lowering, and diabetes therapy should be considered, according to current recommendations ( 96 , 105 108 ). For instance, potential approaches may include metformin, topiramate, aripiprazole augmentation for clozapine patients, or liraglutide, if necessary ( 96 , 105 108 ). Metformin is often preferred for its tolerability and effectiveness ( 105 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation